Prior COVID-19 infection is associated with increased Adverse Events (AEs) after the first, but not the second, dose of the BNT162b2/Pfizer vaccine. Issue 3 (24th January 2022) - Raw, Rachael K.; Rees, Jon; Kelly, Clive A.; Wroe, Caroline; Chadwick, David R.
Abstract: The BNT162b2/Pfizer SARS-CoV-2 vaccine has been widely used in the UK, particularly amongst healthcare workers (HCWs). To establish whether previous COVID-19 influenced vaccine-associated Adverse Events (AEs), we conducted a survey-based study of HCWs in Northeast England. Out of 1238 HCWs, 32% self-reported prior positive PCR and/or antibody test for SARS-CoV-2. Post-dose AEs were worse in those with prior COVID-19 after the first, but not the second dose of vaccine. Second dose AEs were greater in frequency/severity, regardless of COVID-19 history, and they were more systemic in nature. Women and younger HCW were more likely to report AEs after both doses, while dosing interval had no effect on AEs. Ongoing Symptomatic COVID-19 was associated with greater frequency/severity of AEs after dose 2, but not dose one. Overall, AEs were self-limiting and short-lived (i.e., <48 h) in nature. These findings have implications for vaccine hesitancy and informing guidelines for recommended dosing protocols.